Keanekaragaman serangga hama pala (Myristica fragrans) dan tingkat kerusakannya di penyimpanan - Dharmaputra, Okky Setyawati; Sunjaya, Sunjaya; Retnowati, Ina; Nurfadila, Nijma (Jurnal Entomologi Indonesia, 2018)
Pest attack in nutmeg is a cause of major damage both in the field and in storage. Information on the diversity of pest insects in storage, harvesting methods, and good drying needs to be known to reduce the level of damage to nutmeg. This study aims to determine the diversity of insect pests and the percentage of nutmeg damage due to various postharvest treatments. Nutmeg was packed in jute bag and stored for four months under warehouse conditions. Each jute bag containing nutmeg is treated based on the origin of nutmeg (picked from a tree or picked up on the ground), drying method (sunshine or fogging), and shell or without shells with each treatment replicated three times. Sampling of numtag was conducted after four month to calculate the number of each insect species found, determine the insect population, and determine the percentage of damaged seeds. Four insect species were found in nutmeg kernels in almost various treatments. They were Araecerus fasciculatus ((Degeer) (Coleoptera: Anthribidae), Carpophilus dimidiatus (Fabricius) (Coleoptera: Nitidulidae), Oryzaephilus surinamensis (Linnaeus) (Coleoptera: Silvanidae), and Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae). The dominant species was A. fasciculatus. The percentage of damaged kernels derived from nutmeg kernels fallen on the ground, dried either using sun-drying or smoke-drying, either in-shell or without shell, were higher than the kernels derived from ripe fruitswith various treatments. The recommendation of this research result is good postharvest handling of  nutmeg to prevent insect infestation should be conducted by collecting nutmeg derived from ripe fruits picked from the trees, nutmeg in-shell either sun-dried or smoke-dried, and storing nutmeg in-shell.